Reactive template-engaged synthesis of Ni-doped Co3S4 hollow and porous nanospheres with optimal electronic modulation toward high-efficiency electrochemical oxygen evolution. Issue 15 (24th June 2022) - Yang, Bing; Gu, Chengjun; Zhao, Qun; Zhou, Guangyao; Xu, Lin; Pang, Huan
Abstract : Ni-doped Co3 S4 hollow and porous nanoflowers are synthesized via a self-sacrificial reactive template-engaged strategy. The obtained sample with optimal electronic structure exhibits excellent oxygen evolution performance. Abstract : Exploring economical, high-efficiency and durable electrocatalysts for the oxygen evolution reaction (OER) is of critical importance for the advancement of sustainable energy conversion technologies, including water electrolysis and metal–air batteries. Compositional manipulation via heteroatom-doping and nanoarchitectural design of Earth-abundant electrocatalysts are extensively established as valid strategies to effectively optimize the electrocatalytic performance due to the electronic modulation and geometric effect. Herein, we demonstrate a self-sacrificial template strategy for the synthesis of Ni-doped Co3 S4 (denoted as Ni-Co3 S4 hereafter) hollow and porous nanospheres through a straightforward hydrothermal sulfuration treatment. The optimization of Ni incorporation into Co3 S4 could dramatically regulate the electronic state, promote electrical conductivity, and enrich the catalytically active sites, thereby facilitating the OER performance. Furthermore, the hollow spherical nanostructures with permeable walls also allow the increase of the surface-area-to-volume ratio and the electrode–electrolyte contact area. Accordingly, the optimized Ni-Co3 S4 hollow and porous nanospheres with an appropriate Ni content exhibit superior OER properties in 1.0 M KOH electrolyte, as reflected by an overpotential of 298 mV at 10 mA cm −2, a Tafel slope of 90.5 mV dec −1, and a long-term durability of 11 h, making them potential economical electrocatalysts for a myriad of OER-involved energy devices. It is believable that this proposed cation-doping strategy and self-templated synthesis strategy for hollow nanospheres would bring new inspirations for the future rational design of high-efficiency electrocatalysts from both aspects of electronic modulation and nanostructure engineering.